1979
DOI: 10.1104/pp.63.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Peroxidase

Abstract: A major peroxidase has been found in the tomato pericarp (Lycopersicon esculentum var. Tropic) of the ripe and green fruit. A purification scheme yielding this enzyme approximately 85% pure has been developed. The tomato enzyme resembles horseradish peroxidase (HRP) in a standard peroxidase assay and in its ability to be reduced to ferroperoxidase, to be converted to oxyferroperoxidase (compound III), and to form peroxidase complexes with hydrogen peroxide (compounds I and II). In contrast to the HRP, the toma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Tomato anionic peroxidase was extracted from tomato (Lycopersicon esculentum var. tropic) pericarp tissue and purified to about 85% homogeneity as previously described (11). Enzyme concentrations were estimated from the 403 nm A of solutions, using a millimolar extinction coefficient of 107 for the enzyme (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato anionic peroxidase was extracted from tomato (Lycopersicon esculentum var. tropic) pericarp tissue and purified to about 85% homogeneity as previously described (11). Enzyme concentrations were estimated from the 403 nm A of solutions, using a millimolar extinction coefficient of 107 for the enzyme (11).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that tomato anionic peroxidase lacked the capacity to oxidize IAA in the presence of DCP4 and manganous ion as activators, while commercially purified HRP oxidized IAA effectively under the same conditions without a significant lag period (11). The inability of the tomato peroxidase to carry out the oxidation of IAA was then attributed to the low reactivity of the compound II form of the enzyme as compared to HRP compound II.…”
mentioning
confidence: 99%
“…The specific activities of peroxidases of irradiated and non-irradiated plant samples were determined by the method of Kokkinakis and Brooks (1979). The oxidation of guaiacol by peroxidases in the presence of hydrogen peroxide (H 2 O 2 ) was used as the basis for the colorimetric assay based on the development of a reddish color (Doerge et al, 1997).…”
Section: Determination Of Specific Activity Of Peroxidasementioning
confidence: 99%
“…The fractions containing the major peak of peroxidase were combined, concentrated to 2 mL, and dialyzed against 0.02 M NaCl. This enzyme represents the main anionic peroxidase in tomato fruit (14,29 …”
Section: Purification Of Tomato Peroxidasementioning
confidence: 99%
“…The information on tomato peroxidase as an IAA oxidase has been particularly conflicting. Kokkinakis and Brooks (14) measured the oxidation of IAA in citrate buffer and found that the tomato enzyme was much less effective than horseradish peroxidase. They subsequently reported that the oxidation by tomato peroxidase was enhanced by the inclusion of peroxide in the reaction mixture (15).…”
mentioning
confidence: 99%